Differential Viral Distribution Patterns in Reproductive Tissues of Apis mellifera and Apis cerana Drones - Phokasem, Patcharin; Liuhao, Wang; Panjad, Poonnawat; Yujie, Tang; Li, Jilian; Chantawannakul, Panuwan (Frontiers in Veterinary Science, 2021)
Honeybee drones are male bees that mate with virgin queens during the mating flight, consequently transferring their genes to offspring. Therefore, drones’ health affects the overall fitness of the offspring and ultimately the survivability of the colony. Honeybee viruses are one considered to be a major threat to the health of honeybees. Here, we demonstrated the pattern of common honeybee viruses in various tissues of drones in the western honeybee, Apis mellifera, and the eastern honeybee, Apis cerana. Drones were collected during the mating flight and analyzed using qRT-PCR to detect the presence of seven honeybee viruses. The qRT-PCR result revealed that three honeybee viruses, Black Queen Cell Virus (BQCV), Deformed Wing Virus (DWV), and Chinese Sacbrood Virus (CSBV) were detected in A. mellifera and A. cerana drone reproductive tissues. The results from qRT-PCR showed that IAPV was only detected in A. mellifera drone body tissues. Moreover, the prevalence of DWV and BQCV in the drones collected from A. mellifera colonies was significantly higher than that of A. cerana. In addition, virus multiple infections were higher in A. mellifera drones compared to those in A. cerana. CSBV was found predominantly in A. cerana drones’ reproductive tissues. This study is the first report describing the presence of the CSBV in A. mellifera drone reproductive tissues. Our results may reflect the preference of honeybee viruses in honeybee species and may provide an interesting evidence for understanding the virus transmission in A. cerana.